THE DIFFICULT VIRTUE: Reflections on the concept of the general will and its concrete figures - Claudino Oliveira, Higor (Sapere Aude, 2025)
The concept of the general will is a central yet problematic category in the history of political theory. This article offers a critical genealogy of the general will, from Rousseau’s ethical idealism to Hegel’s realist dialectic and Marx’s critique of both. By analyzing the theoretical impasses of liberalism and Jacobinism, the text highlights how the general will cannot be conceived merely as an abstract moral imperative, nor as a mere aggregation of private interests. The study revisits Hegel’s proposal of the bureaucracy as the material bearer of universality and contrasts it with Marx's identification of the proletariat as the class capable of universal emancipation. The analysis culminates in Gramsci's theory of the historical bloc, which integrates pluralism and hegemony into a renewed conception of the general will, overcoming both Rousseau's utopianism and Hegel's corporative realism. The article argues that any democratic theory must confront the challenge of articulating the universal not as an abstract norm but as a historical and social reality mediated by concrete actors. KEYWORDS: general will; pluralism; hegemony; marxism; democracy.